Evaluation Program of Futsal Coaching at the Anak Rantau Club North Sumatera (Journal of Physical Education and Sports, 2020)
The Anak Rantau futsal club as a forum for fostering athlet in the city of Medan to achieve achievements. to improve sports achievement, it is necessary to monitor talent, nursery, and coaching. This study aims to evaluate: Context: Background, Vision Mission, Development program objectives. Input: SDM, facilities and infrastructure availability, funding. Process: training programs implementation, coaches/athletes admision systems, the use of facilities and infrastructure, coordination. Product: achievement and welfare. This study used a qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model developed Stuflebeam. The research subjects included administrators, coaches, athletes, parents. Data collection techniques by observation, interviews, documentation and triangulation. The results showed: first the context of background, vision, mission, program objectives was good and transparent, the second input of on SDM (administrators, coaches, athletes) was good and placed according to their fields, facilities and infrastructure availability at field aspects are inadequate, funding are running poorly because they come from club owners and have not sufficiently fulfilled coaching needs, the third process of regarding the coaching program implementation was quite good according to the training program schedule, athlete recruitment system and good category coordination, while the recruitment system coaches and the use of medium category facilities and infrastructure, trainer recruitment is appointed directly by the management, coordination has been gone very well, the four development program products regarding achievement and welfare were categorized as unstable achievement and the welfare aspects of coaches and athletes were obtained from the results prize when become a champion.